Genetic basis of neurological disease - Wood, Nicholas (Henry Stewart Talks, 2014)
Neurogenetics, Allele frequency vs. effect size, Parkinson’s disease (PD), PINK1: genetic discovery to protein expression, Pink1 and mitochondrial abnormalities, In vivo interaction between PINK1 and Parkin, Parkinsonian proteins and mitophagy, Mitochondrial dysfunction, Protein aggregation, Ceramide metabolism and PD, Lysosomal pathway and PD, Complex trait genetics, Linkage disequilibrium blocks, Identifying common genetic factors, Genetic risk factors & odds of finding variants, First genome-wide association study for PD, Parkinson’s disease molecular pathways, Replicate meta-analysis, The major neurological diseases, Caveats to consider in GWAS, The ENCODE study, Trinucleotide repeats and related disorders, The impact of next generation sequencing